Elements of Nature as the Object of Escapism in Maya Angelouâ€™s â€œWoman Workâ€ - Yustisiana, Rr. Arielia (Universitas Sanata Dharma, 2018)
The research aimed to discuss the elements of nature in the poem entitled â€œWoman Workâ€ written by Maya Angelou. The speaker of the poem used nature as the object of escapism. The research used some theories to meet the topic of discussion. The basic theories of the research were symbol, imagery and figures of speech. They were two figures of speech as the poetic devices in the poem: personification and apostrophe. They were two supporting theories that dealt with the topic, i.e. nature and escapism. There were two approaches that were used: structural and formalistic approaches. Library research is the technique of collecting data. The finding of the research was that the speaker of the poem endowed the elements of nature (which are non-living objects) with human qualities in an attempt to feel less lonely. In the absence of human company, it was the sun, the rain, the snow, dewdrops, the wind, the sky, mountains, oceans, leaves, stones, â€œstar shineâ€ and â€œmoon glowâ€ that were her friends. â€œWoman Workâ€ was a very domestic poem depicting the typical routine life of a woman who performed her daily chores effectively and then yearned for a fantastic break amidst the elements of nature to give her strength and comfort.Â Keywords: nature, escapism, symbol, imagery, personificationÂ